Evaluation of Sex and Age Influence on Plagiarism as Academic Dishonest Behaviour among Postgraduate Students of Federal Universities in South-South Zone of Nigeria - Julius Michael Egbai (International Journal of Educational Administration, Management, and Leadership, 2021)
The study investigated evaluation of sex and age influence on plagiarism as academic dishonest behaviour among postgraduate students of federal universities in South-South, Nigeria. The study which is a survey research, involved a multi-stage stratified random sampling technique of 440 males and 490 females from 3 universities and 3 faculties of the same universities in South-South, Nigeria. The sample was selected through a stratified random sampling approach. The study adopted frequencies, percentages, factor analysis and multiple classification analysis statistical tools. A questionnaire developed and validated by the researcher titled: "Academic Dishonest Behaviour Questionnaire (ADBQ") with Cronbach coefficient alpha reliability of 0.83 was used for data collection. Two research questions and one hypothesis were formulated for the study. The findings indicated that the students used for this study were involved in Sex and Age influence on plagiarism aspect of academic dishonest behaviours. Generally, there is a significant influence of age on plagiarism as academic dishonest behaviour among students. Male students show a positive inclination toward plagiarism on academic dishonest behaviour than their female counterparts while on the other hand, ages 20-24years, show more culpability than other ages. It is therefore recommended among others that there should be synergy among stakeholders in the educational process to fight this menace of Plagiarism.